Polyamines in Plant Biotechnology, Food Nutrition and Human Health - Madhusmita Patra, Chakradhar Patra, S. P. Monalisa (International Journal of Modern Agriculture, 2020)
Polyamines, spermine, spermidine and putrescine also have antioxidant properties and are involved in a variety of organic processes, particularly cell proliferation and differentiation. Dietary polyamines have important consequences for human health, particularly for intestinal growth and immune system differentiation and development. Polyamine plays an important role in preventing the chronic diseases such as cardiovascular diseases, by delivering antioxidants and anti-inflammatory effects. Food is a significant source of polyamines, in addition to endogenous synthesis. While polyamine intake is not recommended daily, it is well known that polyamine requirements are high during stages of fast cell growth (i.e. during the neonatal period). In humans, a general decrease of PA with ageing occurs in conjunction with the certain human health conditions. In the case of Alzheimer's and Parkinson's diseases, high polyamine dose is also detrimental to cancer patients, aging, innate immunity and cognitive impairment. There is a dichotomy since, while polyamine can increase their lifespan and minimize age-related cardiovascular problems, they have negative consequences in conditions of higher cell proliferation. The amount of polyamine in edible plant products as well as food meats should therefore be rigorously quantified. Any food / meats a patient may eat and which are to be avoided can be a guide for the medical experts. In a variety of concentrations, polyamines can be found in every kind of food. Naturally, spermidine and spermine are found in food, while putrescine may also be of microbial origin.